Study and comparison of resource allocation algorithms in a cellular network with relay-assisted D2D Underlay connections - AB, sarah (Latakia University Journal -Engineering Sciences Series, 2025)
Device-to-device (D2D) communication plays a role in meeting data demand, achieving higher data rates, and improving spectral and energy efficiency. The presence of relays improves signal quality and provides a flexible and reliable communication channel for D2D connections. However, when D2D users and cellular users are combined in the same network, it is difficult to effectively allocate resources between these two types of users. This paper addresses the optimization of D2D communication performance and resource allocation using resource allocation algorithms and interference management in both uplink (UL) and downlink (DL) directions to achieve optimal performance in modern cellular networks. It also reviews the use of wireless resource virtualization as a potential solution to increase the demand for mobile data services, provide efficient spectrum utilization, and reduce operating costs. User resource allocation algorithms for uplink and downlink are studied in two parts, the first part includes JUAD (Joint Uplink and Downlink Resource Allocation) and GADIA (Greedy Asynchronous Distributed Interference Avoidance) for uplink, and the second part deals with BIP and Heuristic with WRV (Wireless Resource Visualization) in direct D2D mode and relay-assisted D2D communication mode using MATLAB to improve the efficiency of resource utilization, quality of services provided to users and enhance the efficiency of spectrum utilization, the results showed the superiority of the JUAD algorithm in the uplink case and the BIP algorithm achieved better results in the downlink case.